1970
DOI: 10.3329/bjar.v35i1.5876
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical basis of resistance in eggplant (<i>Solanum melongena</i> L.) to <i>Leucinodes orbonalis</i> Guenee and their correlation with shoot and fruit infestation

Abstract: Studies on the biochemical basis of resistance to Leucinodes orbonalis Guenee and their correlation with shoot and fruit borer damage in five selected brinjal genotypes done at Tamil Nadu Agricultural University, India during June to December 2005 showed that both shoot and fruit of less susceptible genotypes had the higher amount of poly phenol oxidase (PPO), phenylalanine ammonium lyase (PAL) and lignin and lower amount of reducing sugar. Significant negative correlation was found between percent infestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 8 publications
1
9
0
1
Order By: Relevance
“…Fruit infestation exhibited a significantly negative correlation with protein content and total phenol at both levels and only at genotypic level with carbohydrate content. Negative correlation between shoot and fruit borer infestation and polyphenol oxidase has been registered by Doshi (2004) and Khorsheduzzaman et al (2010) It had a positive and significant association with protein content, ascorbic acid and total phenol. Positive correlation between total sugars and shoot and fruit borer infestation has been reported by Doshi (2004), Hazra et al (2004), Shinde et al (2009), Prasad et al (2014) and Ravali et al (2017) and Tiwari et al (2019).…”
mentioning
confidence: 77%
“…Fruit infestation exhibited a significantly negative correlation with protein content and total phenol at both levels and only at genotypic level with carbohydrate content. Negative correlation between shoot and fruit borer infestation and polyphenol oxidase has been registered by Doshi (2004) and Khorsheduzzaman et al (2010) It had a positive and significant association with protein content, ascorbic acid and total phenol. Positive correlation between total sugars and shoot and fruit borer infestation has been reported by Doshi (2004), Hazra et al (2004), Shinde et al (2009), Prasad et al (2014) and Ravali et al (2017) and Tiwari et al (2019).…”
mentioning
confidence: 77%
“…In addition, PPO catalyzes the oxidation of polyphenols and the hydroxylation of monophenols and lignification of plant cells during the rooting process [24] . It is positively correlated with lignin content in both shoot and fruit of eggplant, and the higher amount of PPO and lignin contents improved rooting and resistance to biotic stress [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Sato et al [22] reported that a particular POD catalyzed the process of cell wall lignification during rooting in Zinnia cuttings. PPO catalyzes the oxidation of polyphenols and the hydroxylation of monophenols and lignification of plant cells in trees [23] , [24] . Furthermore, an auxin-induced change in POD and IAAO occurred during the rooting processes [9] .…”
Section: Introductionmentioning
confidence: 99%
“…The activity of POD is reported to be involved in an important step of root formation, during the metabolism of auxin and the process of lignification (Rout, 2006). PPO involved in metabolism of mono-and polyphenols during lignification process in plant cells (Khorsheduzzaman, Alam, Rahman, Mian, & Mian, 2010).…”
Section: Effectiveness Of Naa On Rootings Of Malay Applementioning
confidence: 99%